2008
DOI: 10.1080/09537100802320300
|View full text |Cite
|
Sign up to set email alerts
|

Platelets stimulate airway smooth muscle cell proliferation through mechanisms involving 5-lipoxygenase and reactive oxygen species

Abstract: Continuous recruitment and inappropriate activity of platelets in the airways may contribute to airway remodeling, a characteristic feature of inflammatory airway diseases that includes increased proliferation of the smooth muscle. The aim of the present investigation was to examine the effect of platelets on proliferation of airway smooth muscle cells (ASMC) in culture and to determine the possible role of 5-lipoxygenase (5-LOX) and reactive oxygen species (ROS) in this context. ASMC obtained from guinea pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Disruption of the composition and integrity of cell membranes by degradation of glycoproteins, glycolipids and glycosaminoglycans may also release membrane‐bound growth factors for wound repair . Recent evidence shows that platelet membranes are required to induce synthetic responses in airway smooth muscle cells , perhaps via the trans‐metabolism of platelet‐derived arachidonic acid by smooth muscle 5‐lipoxygenase to produce leukotrienes and the production of reactive oxygen species via NADPH oxidase . The effect of platelets on the synthetic responses of resident structural tissue of the airways might also be supplemented by the ability of platelets to influence the survival, recruitment, proliferation and differentiation of circulating structural cells and stem cells involved in (inappropriate) tissue regeneration .…”
Section: Platelets and Chronic Inflammation/lung Remodellingmentioning
confidence: 99%
“…Disruption of the composition and integrity of cell membranes by degradation of glycoproteins, glycolipids and glycosaminoglycans may also release membrane‐bound growth factors for wound repair . Recent evidence shows that platelet membranes are required to induce synthetic responses in airway smooth muscle cells , perhaps via the trans‐metabolism of platelet‐derived arachidonic acid by smooth muscle 5‐lipoxygenase to produce leukotrienes and the production of reactive oxygen species via NADPH oxidase . The effect of platelets on the synthetic responses of resident structural tissue of the airways might also be supplemented by the ability of platelets to influence the survival, recruitment, proliferation and differentiation of circulating structural cells and stem cells involved in (inappropriate) tissue regeneration .…”
Section: Platelets and Chronic Inflammation/lung Remodellingmentioning
confidence: 99%
“…This result is in line with our previous study, which observed a decrease in ROS levels in the γ-tocotrienol pre-treatment group compared to the PDGF-BB group. Several studies have observed the influence of oxygen species generation in ASM proliferation [ 39 , 61 , 62 ], highlighting the importance of targeting ROS in airway remodeling. The precise mechanism of the antioxidant activity of β-tocotrienol is not fully understood, and further studies are needed to elucidate this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Lipocalin-2 is also elevated in the respiratory secretions of horses with severe asthma [ 44 ] and is further increased in lung tissue after an antigenic exposure [ 48 ]. Other biological processes stimulated by LPS that could have contributed to ASM proliferation include the regulation of the reactive oxygen species metabolic process (through the protein 5-lipoxygenase [ 49 ]) and the regulation of the tumor-necrosis-factor superfamily [ 50 ]. The proteins that are regulated by LPS and were previously shown to be implicated in asthma and in ASM proliferation also include the upregulation of matrix-metalloproteinase-1 (MMP-1) [ 51 ] and Abelson interactor 1 (Abi1) [ 52 ] and the downregulation of insulin-like growth factor-binding protein 2 (IGFBP-2) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%